Biochar-supported polyaniline hybrid for aqueous chromium and nitrate adsorption. (15th October 2021) - Herath, Amali; Reid, Claudia; Perez, Felio; Pittman, Charles U.; Mlsna, Todd E.
Abstract: Biochar adsorbents can remove environmental pollutants and the remediation of Cr(VI) and nitrate are considered. Cr(VI) is a proven carcinogen causing serious health issues in humans and nitrate induced eutrophication causes negative effect on aquatic systems around the world. Douglas fir biochar (DFBC), synthesized by fast pyrolysis during syn gas production, was treated with aniline. Then, a polyaniline biochar (PANIBC) composite containing 47 wt% PANI was prepared by precipitating PANI on DFBC surfaces by oxidative chemical polymerization of aniline in 2M HCl. PANIBC exhibited a point of zero charge (PZC) of 3.0 and 8.2 m 2 /g BET (N2 ) surface area. This modified biochar was characterized by thermogravimetric analysis (TGA), scanning electron microscopy (SEM) morphology and surface elements, and oxidation states by X-ray photoelectron spectroscopy (XPS). PANIBC exhibited positive surface charge below pH 3, making it an outstanding adsorbent, for Cr(VI) removal. Cr(VI) and nitrate removal mechanisms are presented based on XPS analysis. DFBC and PANIBC Cr(VI) and nitrate adsorption data were fitted to Langmuir and Freundlich isotherm models with maximum Langmuir adsorption capacities of 150 mg/g and 72 mg/g, respectively. Cr(VI) and nitrate removal at pH 2 and 6 were evaluated by reducing the amount of PANI (9 wt%) dispersed on to DFBC. Adsorption capacities verses temperature studies revealed that both Cr(VI) and nitrate adsorption are endothermic and thermodynamically favored. Regeneration studies were conducted on both DFBC and PANIBC using 0.1M NaOH and PANIBC exhibited excellent sorption capacities for Cr(VI) and nitrate in lake water samples and in the presence of competitive ions. Graphical abstract: Image 1 Highlights: Composite prepared by precipitation of PANI by oxidative polymerization of aniline. Adsorption capacities for Cr(VI) and nitrate were 150 and 72 mg/g respectively. Three adsorption-regeneration cycles were successfully conducted. Excellent sorption capacities in lake water and with competitive ions.